2009
DOI: 10.1007/s12602-009-9007-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Lactobacillus spp. to Inhibition by Candidate Topical Microbicides

Abstract: Preclinical evaluation of vaginal microbicides includes screening against lactobacilli. However, there is no consensus regarding the species to be tested. This study was carried out to determine if results with one species would apply to other species, and to evaluate the utility of turbidometry as a screening tool. One current (PPCM; previously designated sulfuric acid-modified mandelic acid, SAMMA) and two former (cellulose sulfate, CS; and polystyrene sulfonate, PSS) candidate microbicides were evaluated. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Anderson et al evaluated the inhibitory effect of the microbicides sulfuric acid-modified mandelic acid (SAMMA), polystyrene sulfonate (PSS), and cellulose sulfate (CS) on commercially available lactobacillus spp. and vaginal isolates (66). Their findings indicated selective inhibition of Lactobacillus crispatus and Lactobacillus acidophilus with SAMMA and CS, suggesting differential sensitivity of Lactobacillus spp.…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…Anderson et al evaluated the inhibitory effect of the microbicides sulfuric acid-modified mandelic acid (SAMMA), polystyrene sulfonate (PSS), and cellulose sulfate (CS) on commercially available lactobacillus spp. and vaginal isolates (66). Their findings indicated selective inhibition of Lactobacillus crispatus and Lactobacillus acidophilus with SAMMA and CS, suggesting differential sensitivity of Lactobacillus spp.…”
Section: Figmentioning
confidence: 96%
“…Their findings indicated selective inhibition of Lactobacillus crispatus and Lactobacillus acidophilus with SAMMA and CS, suggesting differential sensitivity of Lactobacillus spp. to the microbicide candidates (66). More recently, a clinical study by Ravel et al indicated a shift in vaginal microbiota from predominantly Lactobacillus spp.…”
Section: Figmentioning
confidence: 99%
“…He also noted that the bactericidal activity of vaginal secretions was associated with lactic acid production due to the fermentation process performed by the bacilli (15). L. acidophilus ais the most abundant bacteria in these environments, and a member of the normal gut and vagina microbiota (16,17). Its role in the human intestinal microbiota is to assist the level of harmful bacteria and fungi lowering and to produce lactase, which is an important enzyme in milk digestion (18).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important for maintaining gastrointestinal health. As a naturally occurring probiotic, Bifidobacteria and Lactobacilli can modify the metabolic activities in the body by modulating immune system [1], producing antimicrobial agents such as hydrogen peroxide, antimicrobial peptides (bacteriocins), and organic acids such as acetic and lactic acids [2]. When used in adequate amounts in diet, they can synthesis vitamins (such as K and B), stabilize barrier functions and enhance the calcium and other mineral absorption on the gut.…”
Section: Introductionmentioning
confidence: 99%